Effect of rainfall in filtration on the stability of residual soil slope / Ahmad Roslan Hairudin - Hairudin, Ahmad Roslan (1993)
It is commonly recognized that when the amount of water present in soil is altered, there is a corresponding change in the characteristics of the soil. This fact lies at the root of every soils problem. The problem of slope stability has always been addressed to soils which are fully saturated. However, many slope failures occur in regions of unsaturated soil. Unfortunately, very little work in this country has been done in the field to actually measure the changes in soil suction and moisture content and incorporate these changes in slope stability analysis. This project proposes to look at the effects of rainwater infiltration into the ground and study the changes of soil properties which govern the strength of the soil and the stability of the slope. It involves laboratory test and field test (installation tensiometer). From the data obtained an analysis is being made and the computer programme is developed. By knowing the duration of the rain, the depth of saturated soil can be calculate, from which the factor of safety is determined.